Study of Hardware Implementation on Size of the Microcalcification Detection Using Embedded Systems - R. Jothilakshmi, G; Mohana Priya, P; K. Suvithra, V (International Journal of Engineering and Technology, 2018)
Detection of microcalcification in glandular breasts is highly critical for early stage cancer detection since, it is very small in size. To detect such smaller microcalcification a hardware device is needed, which is created by the using the digital mammography image from DDSM database the image of malignant breast is acquainted. Two levels of binning is carried out with respect to the RoI to calculate the range of reflection coefficient. Linear mapping of reflection coefficient with mass density is projected as 3D and simultaneously the size of respective second bin is Â calculated to derive the size if the microcalcification .This process is then implemented on hardware to make it more commercial for the people to detect the cancer at an early stage.Â